Cardiorespiratory Fitness Level of College Students in terms of Abdominal Circumference, Body Mass Index, and Gender - Ismi Elya Wirdati; Muhammad Muhibbi; Lutfi Muzaqi; Cahulul Rizaldy Hasan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Cardiorespiratory fitness refers to the integrated ability of the cardiovascular system with the respiratory system to provide oxygen to body tissues and is measured through VO₂max parameters. This variable is related to gender, abdominal circumference, and Body Mass Index (BMI). This cross-sectional study was analytical and involved 43 students as subjects selected by purposive sampling technique. Data were analysed descriptively and analytically using frequency distribution and chi-square test. The majority of the subjects were female (72%), with a mean abdominal circumference of 78.84 cm and included low risk (53%), a mean BMI of 24.88 and included normal (56%), and a mean VO2 max of 11:02 including a very poor category (72%). Correlation tests of gender, abdominal circumference, and BMI with VO2max showed p values of (p=0.000); (p=0.019) and (p=0.645) respectively, which means that there are differences in cardiorespiratory fitness between men and women; there is a statistically significant relationship between abdominal circumference and VO2max level and there is no statistically significant relationship between BMI and VO2max level.  Exploration of the biological mechanisms behind gender disparities and the influence of body fat distribution on VO₂max needs to be studied longitudinally, in addition to testing the effectiveness of integrated interventions in improving the aerobic capacity of at-risk populations..